An extracellular vesicle-related gene expression signature identifies high-risk patients in medulloblastoma. Issue 4 (11th November 2020) - Albert, Thomas K; Interlandi, Marta; Sill, Martin; Graf, Monika; Moreno, Natalia; Menck, Kerstin; Rohlmann, Astrid; Melcher, Viktoria; Korbanka, Sonja; Meyer zu Hörste, Gerd; Lautwein, Tobias; Frühwald, Michael C; et al.
Abstract: Background: Medulloblastoma (MB) is a malignant brain tumor in childhood. It comprises 4 subgroups with different clinical behaviors. The aim of this study was to characterize the transcriptomic landscape of MB, both at the level of individual tumors as well as in large patient cohorts. Methods: We used a combination of single-cell transcriptomics, cell culture models and biophysical methods such as nanoparticle tracking analysis and electron microscopy to investigate intercellular communication in the MB tumor niche. Results: Tumor cells of the sonic hedgehog (SHH)–MB subgroup show a differentiation blockade. These cells undergo extensive metabolic reprogramming. The gene expression profiles of individual tumor cells show a partial convergence with those of tumor-associated glial and immune cells. One possible cause is the transfer of extracellular vesicles (EVs) between cells in the tumor niche. We were able to detect EVs in co-culture models of MB tumor cells and oligodendrocytes. We also identified a gene expression signature, EVS, which shows overlap with the proteome profile of large oncosomes from prostate cancer cells. This signature is also present in MB patient samples. A high EVS expression is one common characteristic of tumors that occur in high-risk patients from different MB subgroups or subtypes. Conclusions: With EVS, our study uncovered a novel gene expression signature that has a high prognostic significance across MB subgroups.